Pope Benedict XVI's legal thought : a dialogue on the foundation of law - Cartabia, Marta; Simoncini, Andrea (Law professor) (Cambridge Cambridge University Press, 2015)
"Throughout Pope Emeritus Benedict XVI's pontificate he spoke to a range of political, civil, academic, and other cultural authorities. These speeches reveal a striking sensitivity to the fundamental problems of law, justice, and democracy. He often presented a call for Christians to address issues of public ethics such as life, death, and family from what they have in common with other fellow citizens: reason. This book discusses the speeches in which the Pope Emeritus reflected most explicitly on this issue, along with commentary from distinguished legal scholars. It responds to Benedict's invitation to engage in public discussion on the limits of positivist reason in the domain of law from his address to the Bundestag. Although the topics of each address vary, they are joined by a series of core ideas whereby Benedict sketches, unpacks, and develops an organic and coherent way to formulate a 'public teaching' on justice and law"--
Machine generated contents note: 1. A journey with Benedict XVI through the spirit of constitutionalism Marta Cartabia and Andrea Simoncini; Part I. Law, Reason, and Religion: 2. Reality and transcendence: more than a religious issue Armin von Bogdandy and Sergio Dellavalle; 3. Human dignity without God? Reflections on some relevant speeches of Benedict XVI Rafael Domingo; 4. The windows of Benedict XVI: reason, revelation, and law Wael Farouq; 5. The secular state, democracy, and natural law: Benedict XVI's address to the Bundestag from the perspective of legal ethics and democracy theory Martin Rhonheimer; 6. From Regensburg to Berlin - holiness and reason: a reflection on Pope Benedict XVI's public lectures J. H. H. Weiler; 7. 'To serve right and to fight wrong': why religion, human rights, and human dignity need each other John Witte, Jr; Part II. Fundamental Rights and Freedom of Religion: 8. Faith and reason in the Regensburg address Giuliano Amato; 9. Religious freedom in the political speeches of Pope Benedict XVI Mary Ann Glendon; 10. Freedom of religion - the contribution of Benedict XVI to a universal guarantee from a European perspective Christoph Grabenwarter; 11. Benedict's legacy: human rights, human dignity, and the possibility of dialogue Christopher McCrudden; Part III. Democracy in a Society of 'Others': 12. Concerning the doctrine of democracy in Benedict XVI Massimo Luciani; 13. Acting contrary to reason is contrary to God's nature Andre;s Ollero; 14. A listening heart: where democracy begins Andrea Pin.
Keywords: Benedict -- XVI, -- Pope, -- 1927- -- Political and social views; Catholic Church -- Doctrines; Law -- Philosophy; Canon law; Christian sociology -- Catholic Church; LAW / Jurisprudence